Wood Chile peppers stalks-plastic composite production - J. Valles-Rosales, Delia; C. Méndez-González, Luis; A. Rodríguez-Picon, Luis; del Valle-Carrasco, Arturo; A. Alodan, Haytham (Maderas. Ciencia y Tecnología, 2016)
Nowadays, most common wood fibers used to produce wood plastic composites are from Oak and pine trees, rice hull, recycled paper, pallets and post-industrial oak fiber, furniture waste, or cedar wood chips. This paper is focused on a new wood plastic composites based on pre-dried New Mexico red chile stems and leafs with high-density polyethylene. The specimens were manufactured following ASTM 638-9 standard using injection molding. A series of experiments were designed to investigate how wood fiber length, geometry, and water absorption affects the microcellular structure of the new sustainable material. The effects of proportions and particle size on the strength of the resulting blend were analyzed. It was found that larger particle sizes of wood fiber showed higher mechanical properties. The blending of additives in the new sustainable material has shown to increase proper fiber dispersion improving the strength of the material.